Characterization of the NAC gene family in ‘Fengdan’ peony (Paeonia ostii) insights into the evolution and expression patterns under abiotic stresses and ABA treatment - Yu, Xiangli; Meng, Qirui; Hou, Hongyan; Guo, Qiang; Wang, Qingjie; Yang, Yuqing; Zhang, Yanzhao (Frontiers in Plant Science, 2025)
BackgroundAs one of the largest plant-specific transcription factor families, NAC proteins are crucial for plant growth and development processes and responses to various abiotic and biotic stresses. The published sequenced chromosome-level genome of ‘Fengdan’peony provides a powerful tool for the analysis of the NAC gene family in this shrub.MethodsThe PoNAC gene family was identified and characterized using bioinformatic analysis, and RT-qPCR analysis was performed on some PoNACs from the ATAF and NAP subfamilies.ResultsIn this study, a total of 82 NAC transcription factors (TFs) were identified in the ‘Fengdan’ peony genome, with the uneven anchorage of 78 PoNAC genes on 5 chromosomes, whereas only 4 PoNAC genes were found to be located on unanchored scaffolds. Through the phylogenetic analysis, 66 PoNAC genes were classified into 15 distinct subfamilies. The gene structure analysis revealed the variation in the number of exons from 0 to 14. Moreover, the motif analysis indicated that the identified PoNAC TFs possessed conserved NAC domains and motifs. The duplication events of PoNAC genes included whole-genome duplications (WGDs) or segmental duplications for 14 pairs, tandem duplications for 2 pairs, and proximal duplications for 3 pairs. GO analysis results suggested that the functions of PoNAC genes were mostly concentrated in the “biological process” GO category. Additionally, the analysis of the expression profiles of PoNAC genes in different plant organs revealed that only 45 genes were expressed in various tissues, some of them exhibited tissue-specific expression related to plant growth and development. RT-qPCR experiments demonstrated the responses of 8 genes from the ATAF and NAP subfamilies to ABA, heat and drought, suggesting that they may serve as important regulatory factor.